2010
DOI: 10.1038/nature09342
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic memory in induced pluripotent stem cells

Abstract: Summary Somatic cell nuclear transfer and transcription factor-based reprogramming revert adult cells to an embryonic state, and yield pluripotent stem cells that can generate all tissues. These two reprogramming methods reset genomic methylation, an epigenetic modification of DNA that influences gene expression, by different mechanisms and kinetics, leading us to hypothesize that the resulting pluripotent stem cells might have different properties. Here we observe that low passage induced pluripotent stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

69
1,736
8
18

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,034 publications
(1,872 citation statements)
references
References 53 publications
69
1,736
8
18
Order By: Relevance
“…One analysis on the whole genome scale found 71 differentially methylated regions (DMR) between three iPSC lines and three ESC lines (and 2,179 between fibroblasts and iPSC) [57]. Almost half of the DMRs show incomplete epigenetic reprogramming of the differentiated cell-of-origin genome, which is in agreement with the gene expression data [24] and epigenetic memory [58]. However, not all the DMR belong to the cell-of-origin memory, indicating that iPSC also accumulate novel aberrant epigenetic states [57,59].…”
Section: Epigenetic Comparison Between Ipsc and Escsupporting
confidence: 59%
“…One analysis on the whole genome scale found 71 differentially methylated regions (DMR) between three iPSC lines and three ESC lines (and 2,179 between fibroblasts and iPSC) [57]. Almost half of the DMRs show incomplete epigenetic reprogramming of the differentiated cell-of-origin genome, which is in agreement with the gene expression data [24] and epigenetic memory [58]. However, not all the DMR belong to the cell-of-origin memory, indicating that iPSC also accumulate novel aberrant epigenetic states [57,59].…”
Section: Epigenetic Comparison Between Ipsc and Escsupporting
confidence: 59%
“…3A) as reported in earlier findings (Li et al ., 2009; Kim et al ., 2010; Cheng et al ., 2011; Wang et al ., 2011; Rohani et al ., 2014). We reprogrammed SkMs from both young and old mice using classic Yamanaka factors, and colonies were stained with alkaline phosphatase (ALP) on day 16–18 and counted to assess reprogramming efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that older and senescent cells are more resistant to reprogramming (Li et al ., 2009; Kim et al ., 2010; Cheng et al ., 2011; Wang et al ., 2011; Rohani et al ., 2014). These observations have established the importance of current efforts underway to understand the biology of cell reprogramming in the context of chronological and replicative age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50,51 In the case of iPS cells, the process of ectopic induction of pluripotency might somehow interfere with its usefulness as a biological model for germ cell formation. [52][53][54] The same is true for the facts, that the epigenetic memory of the original differentiated state is not perfectly erased during reprogramming 55,56 and that iPS cells have been reported to accumulate karyotypic abnormalities and gene mutations during propagation in culture. [57][58][59][60] AFS very likely do not harbour accumulated somatic mutations, because they are primary cells of a very early stage of human development.…”
Section: Amniotic Fluid Stem (Afs) Cells Could Be a Useful Tool To Stmentioning
confidence: 85%